2021
DOI: 10.1093/jhered/esab010
|View full text |Cite
|
Sign up to set email alerts
|

Genome Assembly of SalicaceaePopulus deltoides(Eastern Cottonwood)I-69Based on Nanopore Sequencing and Hi-C Technologies

Abstract: Populus deltoides is of significantly ecological and economic values, widely used in poplar breeding programs due to its superior characteristics such as rapid growth and resistance to disease. Although the genome sequence of P. deltoides WV94 is available, the assembly is fragmented. Here, we reported an improved chromosome-level assembly of the P. deltoides cultivar I-69 by combining Nanopore sequencing and chromosome conformation capture (Hi-C) technologies. The assembly was 429.3 Mb in size and contained 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…In order to investigate the advantage of the integrated linkage map over the two parental linkage maps, we first compared their consensuses with the genomic sequences of P. simonii [ 25 ] and P. deltoides [ 31 ]. We found that a total of 68 local regions on the integrated linkage map were discordant with the P. simonii genomic sequence, which contained ~15% (173) of all the RAD tags ( File S1 ; Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to investigate the advantage of the integrated linkage map over the two parental linkage maps, we first compared their consensuses with the genomic sequences of P. simonii [ 25 ] and P. deltoides [ 31 ]. We found that a total of 68 local regions on the integrated linkage map were discordant with the P. simonii genomic sequence, which contained ~15% (173) of all the RAD tags ( File S1 ; Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the two parent-specific linkage maps, the integrated linkage map was more consensus with the genomic sequences of P. simonii [ 25 ] and P. deltoides [ 31 ]. Although the available genomic sequences have some shortcomings due to the complexity of genomic assembling, such consensus reflects a certain degree of authenticity in the order of contigs because the genomic assemblies and genetic maps were obtained using independent technologies.…”
Section: Discussionmentioning
confidence: 99%
“…After the release of this landmark genomic resource, other high-quality reference sequences have been recently assembled for eastern cottonwood clone W94 ( (accessed on 22 March 2022)), and for cultivar I-69, which shows 97.4% of anchored sequences and only 0.08% of gaps ( Table 4 ) [ 59 ]. Additional reference sequences have been assembled and annotated for P. pruinose [ 54 ], desert poplar ( P. euphratica ) [ 55 , 56 ], the two aspen species P. tremula and P. tremuloides [ 4 ], white poplar [ 3 , 57 ], P. simonii [ 58 ], and the hybrid P. alba × P. tremula var.…”
Section: Genome Sequences Are Pivotal To Improve Poplar Breeding For ...mentioning
confidence: 99%
“…Overall, more than 45,000 protein-coding genes were annotated on poplar genomes and their functional characterization represents a powerful tool to help dissecting the genetic bases of biotic stress resistance and accelerating poplar breeding [ 4 , 59 ]. For instance, the gene ontology (GO) classification carried out on European aspen and quacking aspen genome sequences allowed the identification of genes putatively involved in disease resistance [ 4 ].…”
Section: Genome Sequences Are Pivotal To Improve Poplar Breeding For ...mentioning
confidence: 99%
“…Several high-quality poplar genomes have become available, including P. trichocarpa (Torr. and Gray) 3 , P. euphratica Oliv 5 , P. alba 6 and P. deltoides 7 , which belong to section Tacamahaca, Turanga, Populus and Aigeiros, respectively. These four species and P. wilsonii grow in different environments and occur across diverse habitats.…”
mentioning
confidence: 99%